Personality and Teamwork on Employee Performance Through Organizational Commitment - Nuramalia Syam; Sahade Sahade; Masnawaty Masnawaty (PINISI Discretion Review, 2023)
This study aims to determine the entertainment tax revenue and recreation area retribution, to determine the entertainment tax revenue and recreational area retribution in increasing the PAD of Bulukumba Regency. The variables in this study are entertainment tax, recreation area retribution as free and local revenue as the variables. The sample in this study is the Realization of Regional Original Revenue (PAD) for the 2015-2021 fiscal year, using data collection techniques, namely documentation. This study uses a quantitative descriptive analysis technique. The results of this study are: the Bulukumba Regency Government which is shown by the Regional Revenue and Finance Management Agency from 2015-2021 has carried out an effective entertainment tax collection even though revenue tends to fluctuate and only 2016 entertainment tax revenue is above the set target. Meanwhile, the collection of retribution for recreation areas from 2015- 2021 is still less effective as indicated by the average level of effectiveness of receiving retribution for recreation areas, which is only 77% which is in the less effective criteria. from 2015-2021 by 0.02% which is in the criteria of very less contributing. Likewise, the receipt of retribution for recreation areas in increasing PAD from 2015-2021 has a very low contribution as evidenced by its contribution of 2.53% which is in the very low criteria.